Evaluación del Daño y Manejo del gusano cogollero (Spodoptera frugiperda) en el cultivo de maíz suave (Zea mays L.) en el sector Las Parcelas, cantón Mira - Guerrero Obando, Edison Daniel (2018)
SUMMARY The present work was carried out in order to solve a need of farmers in the area, which consists in the observation and identification of the corn cogollero worm, since the corn crop in the area is the main crop that It has been maintained for a long time, it is an ancestral crop and it will continue to be cultivated since it depends on the daily diet of those who grow it and of the whole country. In the document is described the characteristics, morphology of the pest, the taxonomic classification, the damages, symptoms and signs that are given in the plants by the attack and the problems that this plague causes to the farmer, since if it is not controlled time can cause very large economic losses. Identify according to the phenology of the crop, the times of attack of the pest and the environmental conditions more propitious for the attack. A survey was also carried out to farmers, to show the reality of what is happening with the management and control of the pest in the crop and to know what type of management they are implementing.